Induction of ferroptosis in human nasopharyngeal cancer cells by cucurbitacin B: molecular mechanism and therapeutic potential - Huang, Shuai; Cao, Bihui; Zhang, Jinling; Feng, Yunfei; Wang, Lu; Chen, Xiaopei; Su, Hang; Liao, Shengrong; Liu, Jinggong; Yan, Jun; Liang, Baoxia (Cell death & disease, 2021)
Cucurbitacin B (CuB) is a widely available triterpenoid molecule that exhibits various biological activities. Previous studies on the anti-tumour mechanism of CuB have mostly focused on cell apoptosis, and research on the ferroptosis-inducing effect has rarely been reported. Herein, we first discovered the excellent cytotoxicity of CuB towards human nasopharyngeal carcinoma cells and elucidated its potential ferroptosis-inducing mechanisms. Morphology alterations of mitochondrial ultrastructure, as observed via transmission electron microscopy, showed that CuB-treated cells undergo ferroptosis. CuB caused intracellular accumulation of iron ions and depletion of glutathione. Detailed molecular mechanism investigation confirmed that CuB both induced widespread lipid peroxidation and downregulated the expression of GPX4, ultimately initiating a multipronged mechanism of ferroptosis. Furthermore, CuB exhibited anti-tumour effects in vitro by inhibiting cellular microtubule polymerization, arresting cell cycle and suppressing migration and invasion. Finally, CuB significantly inhibited tumour progression without causing obvious side effects in vivo. Altogether, our study highlighted the therapeutic potential of CuB as a ferroptosis-inducing agent for nasopharyngeal cancer, and it provided valuable insights for developing effective anti-tumour agents with novel molecular mechanisms derived from natural products.